Speech development in children with autism spectrum disorders (ASD) - Ansimova A. I. (Scientific studies and modern education, 2024)
This article examines language development in children with ASD, providing an overview of theoretical approaches and empirical evidence. The article reveals key characteristics of speech development in ASD, such as delays in speech development, difficulties with understanding language and pragmatic aspects of speech.
Keywords: развитие речи; коммуникативные трудности; speech development; расстройство аутистического спектра; РАС; speech therapy; ASD; речевая терапия; communication difficulties